"Alcohol intoxication by proxy on a NICU" - a case report - Ulrike Wurst; Benjamin Ackermann; Wieland Kiess; Ulrich Thome; Corinna Gebauer (BMC, 2022)
Abstract Background Ethanol intoxications in newborns are generally due to false preparation of formula with alcoholics or alcohol consumption by the breastfeeding mothers. Rarely, intoxications occur in hospitalized newborns, e.g., from excessive use of alcoholic hand sanitizers. We herein report a strange case of acute ethanol intoxications in our NICU. Case presentation An extremely premature infant (23 0/7 weeks gestational age, birthweight 580 g) suffered from repeated life-threatening events with hemodynamic compromise, apnea, and lactic acidosis while being treated in our neonatal intensive care unit (NICU). Symptomatic treatment with intravenous fluids and, if necessary, intubation and catecholamine therapy led to recovery after several hours each time. The episodes eventually turned out to be severe ethanol intoxications brought about by breast milk contaminated with ethanol. The breast milk was supplied by the infant's mother, who consumed non-trivial amounts of alcohol to build up her strength and make herself produce more milk, which was recommended to her by a family member. Additionally, she supplemented her own mother's milk with cow's milk because she was worried her baby was underserved with her milk. The mother admitted to this in intensive conversations with our team and a professional translator. Conclusions This unique case underlines how different cultural dynamics can attribute to life-threatening events in the care of premature infants. It is important for us to emphasize that intensive communication and building a confident relationship with the parents of patients is essential to the work on NICUs. Child safeguarding issues and possibilities of intoxications have to stay in mind even in a supposedly safe space like the NICU.